(untitled) (London Journal of Medical and Health Research, 2025)
Introduction: Soft tissue injuries in post-traumatic fractures are a clinical challenge, associated with high complication rates. Negative Pressure Wound Therapy (NPWT) has emerged as a promising alternative to traditional dressings. Objective: To evaluate, through a systematic review, the efficacy of Negative Pressure Wound Therapy (NPWT) compared to traditional dressings in the treatment of soft tissue injuries in patients with fractures. Methods: A systematic literature review was conducted in the PubMed, SciELO, and LILACS databases, including articles published between 2010 and 2025. Six studies were included in the final qualitative synthesis. Results: The evidence indicates that NPWT is superior to traditional dressings in reducing healing time and decreasing infection rates, particularly in lower limb fractures. However, the benefits regarding the reduction of hospitalization time and the need for surgical reinterventions are inconsistent in the literature. The cost-effectiveness of NPWT proved to be controversial and dependent on the healthcare system context, and data on long-term functional outcomes are scarce. Conclusion: NPWT is an effective and preferential therapeutic tool for managing complex wounds associated with fractures, primarily for accelerating healing and reducing infection risk. The decision for its use, however, must be carefully considered, taking into account the controversies regarding its cost-effectiveness, the heterogeneity of the evidence, and the patient’s clinical profile.